Analysis of dynamic variations and origin predominating pollutants in Qiandao Lake - LÜ Huan-chun; CHEN Ying-xu; YU Zuo-ming; WANG Fei-er; FANG Zhi-fa (浙江大学学报. 农业与生命科学版)
In this paper the dynamic variation of predominating pollutants in Qiandao Lake based on statistical analysis of routine monitoring data from 1989 to 1999 are presented and the origin of those pollutants are discussed. Chemical analysis showed that nitrogen and phosphorus were the main contaminants of the water body, and the annual average concentrations of total nitrogen (TN) and total phosphorus (TP) fluctuated widely. The concentrations of TN and TP reached the level Ⅲ-Ⅴ with maximum concentration being about 10 times of the standard level, which was much higher than permissive level stipulated by China Environmental Quality Standard for lake and reservoir water quality (GHZB1-1999). The pollution of upstream Xin'an River and the southwest corner was very severe, and pollution of the central part and the southeast corner of the lake was less serious. Soil and water loss by run-off and soil erosion and fertilizer and pesticide leaching resulted from sloping field assart and inadequate forestation were the main factors leading to eutrophication of the lake.